Genetic and Clinical Profiles of Pheochromocytoma and Paraganglioma: A Single Center Study - Ma, Xiaosen; Li, Ming; Tong, Anli; Wang, Fen; Cui, Yunying; Zhang, Xuebin; Zhang, Yushi; Chen, Shi; Li, Yuxiu (Frontiers in Endocrinology, 2020)
Pheochromocytoma/paraganglioma (PPGL) has a high genetic heterogeneity with 40% germline variants in known pathogenic genes. Data in Chinese on this aspect are scanty. To detect the genetic and clinical profile of Chinese PPGL patients. We examined the variants of 12 known germline pathogenic genes (SDHA, SDHB, SDHC, SDHD, SDHAF2, FH, VHL, RET, NF1, MAX, TMEM127 and KIF1B) by next generation sequencing and Sanger sequencing in 314 Chinese PPGL subjects. Twenty nine percent of Chinese PPGL patients had germline variants and SDHB was the most frequently mutated (14.6%). The most frequent SDHB variants were in exon 2, exon 7 and IVS 7. Pathogenic variants were more likely to occur in metastatic PPGL patients, paragangliomas and patients under 30, with the ratio being 50.7% (35/69), 35.9% (56/156), and 49.5% (52/105), respectively. Our cohort included 314 patients from a single setting. The genetic and clinical features of Chinese PPGL patients were unique in some aspects compared to their non-Chinese counterparts. Identification of genotype-phenotype relation can serve as an effective tool for genetic prioritization and clinical decision-making.